Estado de los procesos de valoración ocupacional de las personas con discapacidad en Colombia: Un análisis exploratorio. - Cárdenas-Jiménez, Andrea; Moreno-Angarita, Marisol; Álvarez-Montaña, Diana L. (Revista de Salud Pública, 2013)
Objective This paper analyses a study of the current state of occupational assessment of disabled people; it took place in 14 public and private institutions involved in promoting the inclusion of this population in the workforce. The study was aimed at providing definitions, demonstrating the pertinent processes, instruments, professionals, stages of the process and support involved in helping disabled people to become included in the workforce. Methodology The study involved a group of experts adopting a methodology which designed, implemented and analysed a data collection instrument seeking qualitative and quantitative data concerning target populations, assessment purposes, the instruments used, timing and other relevant factors for programmes aimed at disabled people becoming included in the workforce. The 14 Colombian institutions having most experience regarding this topic participated in the study (the oldest having 40 years' experience and the most recent 8 years in this field). Results The results indicated widespread heterogeneity regarding the occupational assessment components explored. It was found that the objectives proposed for each process differed, depending on each institution's philosophy and structure, the model's characteristics and those of the intraprofessional teams. They also highlighted the broad range of instruments and timing (i.e. 1 to 180 days) of subprocesses used as tools for occupational assessment (of the disabled). Conclusions These findings constitute a foundation justifying the compilation of a Manual for the Occupational Assessment of Disabled People in Colombia, recognising accumulated cognitive, social and professional capital (i.e. established tradition in this field).